2016
DOI: 10.1016/j.ejmech.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of furoxan derivatives against Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) remains a serious health problem responsible to cause millions of deaths annually. The scenario becomes alarming when it is evaluated that the number of new drugs does not increase proportionally to the emergence of resistance to the current therapy. Furoxan derivatives, known as nitric oxide (NO) donors, have been described to exhibit antitubercular activity. Herein, a novel series of hybrid furoxan derivatives (1,2,5-oxadiazole 2-N-oxide) (compounds 4a-c, 8a-c and 14a-c) were designed, synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 57 publications
0
36
0
1
Order By: Relevance
“…Moreover, there is ad irect correlation between NO-donorc apability and antitubercular activity:t he more powerful NO-donor hybrid among the series is the most active antitubercular agent. [37] As eries of furoxan-based chalcone hybridsw as synthesized through Wittig reaction of polymer-supported phosphonium ylides 37 a-c with furoxancarbaldehydes 26 a,b (Scheme 14). The resulting derivatives 39 a,b are not mutagenic and can be considered promisingi nvivop hase II enzyme inducers,w hich is very useful in chemopreventive cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is ad irect correlation between NO-donorc apability and antitubercular activity:t he more powerful NO-donor hybrid among the series is the most active antitubercular agent. [37] As eries of furoxan-based chalcone hybridsw as synthesized through Wittig reaction of polymer-supported phosphonium ylides 37 a-c with furoxancarbaldehydes 26 a,b (Scheme 14). The resulting derivatives 39 a,b are not mutagenic and can be considered promisingi nvivop hase II enzyme inducers,w hich is very useful in chemopreventive cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of furoxan-hydrazonehybrids linked via phenol bridge. [37] Reagents and conditions:a )o-, m-, or p-HOC 6 H 4 CHO,D BU, CH 2 Cl 2 ,R T; b) isonicotinic hydrazide,H Cl (cat. ), EtOH, RT,1 2h,8 3-95 %.…”
Section: Introductionmentioning
confidence: 99%
“…bicyclic nitroimidazoles) have shown Mtb-killing activity [39,40]. Furthermore, NO donor compounds such as DETA/NO, S-nitrosothiols, and furoxan derivatives have also demonstrated anti-Mtb activity in preclinical models [41][42][43]. Despite the efficacy in preclinical models, there has been limited evidence on the efficacy of NO donor compounds in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, compound ( 25 ) (Figure 9) exhibited MIC 90 of 7 μM against MDR-TB clinical isolates. Furthermore, the authors have demonstrated that this compound may act through the release of nitric oxide [48]. Smith and coworkers have discovered a nitrotriazole derivative as a promising antitubercular agent.…”
Section: Antituberculosis Compoundsmentioning
confidence: 99%